Motor engagement enhances incidental memory for task-irrelevant items - Shimane, Daisuke; Tanaka, Takumi; Watanabe, Katsumi; Tanaka, Kanji (Frontiers in Psychology, 2022)
Actions shape what we see and memorize. A recent work indicates that incidental memory for task-irrelevant items increased by concurrent action execution. On the other hand, another line of studies suggests that task-irrelevant items were better encoded when they were presented with cues requiring cognitive and motor responses than with distractors (i.e., attentional boost effect). Thus, the direct link between the engagement of the motor system (motor engagement) and memory encoding remains unclear. To identify the impact of motor engagement, we investigated whether action enhances memory for items temporally separated from the behavioral cue. In our pre-registered online experiment (N = 142), participants responded to visual Go cues by pressing a key (i.e., motor task) or counting (i.e., cognitive task) while ignoring No-go cues. In each trial, two task-irrelevant images were sequentially presented after the cue. After the encoding Go/No-go task, participants performed a surprise recognition memory test for those images. We did not observe memory differences between Go and No-go trials in the motor task nor between motor and cognitive Go trials. This means action execution itself was not critical for memory enhancement. However, only for the items presented away from the cues in time, the memory performance in the motor No-go trials was higher than that in the cognitive No-go trials. Therefore, engaging in the motor task itself could increase incidental memory for the task-irrelative items compared to a passive viewing situation. We added empirical evidence on the online interaction between motor engagement and memory encoding. This may expand our understanding of everyday memory such as active learning.